A flexible porous chiral auxetic tracheal stent with ciliated epithelium. (1st April 2021) - Liu, Jiapeng; Yao, Xinhua; Wang, Zhenwei; Ye, Jian; Luan, Congcong; He, Yong; Lin, Hui; Fu, Jianzhong
Abstract: Tracheal stent placement is a principal treatment for tracheobronchial stenosis, but complications such as mucus plugging, secondary stenosis, migration, and strong foreign body sensation remain unavoidable challenges. In this study, we designed a flexible porous chiral tracheal stent intended to reduce or overcome these complications. The stent was innovatively designed with a flexible tetrachiral and anti-tetrachiral hybrid structure as the frame and hollows filled with porous silicone sponge. Detailed finite element analysis (FEA) showed that the designed frame can maintain a Poisson's ratio that is negative or close to zero at up to 50% tensile strain. This contributes to improved airway ventilation and better resistance to migration during physiological activities such as respiration and neck movement. The preparation process combined indirect 3D printing with gas foaming and particulate leaching methods to efficiently fabricate the stent. The stent was then subjected to uniaxial tension and local radial compression tests, which indicated that it not only has the same desirable auxetic performance but also has flexibility similar to the native trachea. The porous sponge facilitated the adhesion of cells, allowed nutrient diffusion, and would prevent the ingrowth of granulation tissue. Furthermore, a ciliated tracheal epithelium similar to that of the native trachea was differentiated from normal human bronchial primary epithelial cells on the internal wall of the stent under air-liquid interface conditions. These results suggest that the designed stent has the potential for application in the treatment of tracheobronchial stenosis. Graphical abstract: Image, graphical abstract